2017
DOI: 10.1063/1.4978114
|View full text |Cite
|
Sign up to set email alerts
|

Physical-chemical quality of onion analyzed under drying temperature

Abstract: Abstract. Drying is one of conventional processes to enhance shelf life of onion. However, the active compounds such as vitamin and anthocyanin (represented in red color), degraded due to the introduction of heat during the process. The objective of this research was to evaluate thiamine content as well as color in onion drying under different temperature. As an indicator, the thiamine and color was observed every 30 minutes for 2 hours. Results showed that thiamine content and color were sensitvely influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Generally, the drying process needs amount of heat provided by hot air [30]. Reis et al [31] reported that capsaicin content degraded by the increase of temperature.…”
Section: Kinetics Models Of Capsaicin Degradationmentioning
confidence: 99%
“…Generally, the drying process needs amount of heat provided by hot air [30]. Reis et al [31] reported that capsaicin content degraded by the increase of temperature.…”
Section: Kinetics Models Of Capsaicin Degradationmentioning
confidence: 99%
“…In Morocco, onion moisture can reach a value between 87.80% and 92.30%. However, according to several studies, onion moisture was estimated between 70% and 90% [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial and final moisture content (% wet basis) of some commonly used agricultural commodities along with their maximum allowable drying temperature is given in Table 1. [21][22][23][24][25][26][27][28][29][30][31][32][33] There are three main types of solar dryers depending on the mode of heat transfer to the drying chamber. The first is the direct solar dryers, where solar radiations were allowed to strike the drying chamber by passing through a transparent wall.…”
Section: Introductionmentioning
confidence: 99%